The impact of people’s participation on public policy satisfaction in Vietnam - Trung, Phan Nhan (Masyarakat, Kebudayaan dan Politik, 2024)
People’s participation in public decision-making not only helps ensure transparency and accountability but also contributes to improving their satisfaction with government policies and operations. This study examines whether transparency in decision-making, trust in public agencies, access to information, and people’s awareness of their rights and responsibilities play an important role in promoting their participation. The study also explores whether this participation directly affects people’s satisfaction with public decisions and policies. This study uses mixedmethod approach through the SEM linear regression model. The analysis of the results shows that transparency, trust, information accessibility and citizen awareness have a positive and significant impact on the level of their participation in public activities. However, increased participation does not necessarily lead to higher levels of satisfaction with public policies, especially when the participation process does not meet people’s expectations or lacks transparency and efficiency. The study concludes that, to improve people’s satisfaction, it is necessary not only to promote participation, but also to improve the quality of this process, ensuring that participation is substantive and has a clear impact on public decisions. As such, specific recommendations are made to improve public policy and enhance people’s participation and satisfaction in the context of modern public governance.